The role of balanced centricity on service ecosystems development: an analysis of new business models - Quero-Gervilla, María José; Ventura-Fernández, Rafael (My University, 2017)
Purpose – The purpose of this paper is to propose that for a service ecosystem to arise, there is a need for all the stakeholders to seek for balanced centricity at the micro, meso and macro context. For new collaborative models, can be considered the basis for value co-creation into ecosystems. Design/Methodology/approach – The authors apply a conceptual approach to develop and propose a framework for deepening understanding balanced centricity as the basis for value co-creation at every level of the service ecosystem. Qualitative case study research was conducted with different methods of data generation including interviews and participant observation. Findings –New business models need new strategies as all the actors exchange resources looking for the benefit of the whole system. In this sense, authors argue for considering balanced centricity as an strategy that enables the ecosystems to arise. From this perspective, balanced centricity should be developed at every level of the ecosystem (micro, meso and macro). Research limitations/implications (if applicable) – The paper is a conceptual paper that combines with an empirical approach. The empirical approach only considers five success cases on the arts sector. Other sectors different from the cultural and other countries would be useful to add new perspectives to the theory development. Practical implications (if applicable) – Although sometimes an ecosystem arises in a natural way into markets, the configuration and development of Balanced Centricity as a strategy would be useful in order to both: increase value co-creation among existing ecosystems and facilitation of ecosystems development. As ecosystems arising is considered a desired fact, innovation into public universities have found into this strategy a model to foster and develop new businesses. It is the case of Link by UMA Tech, wich in the context of the University of Málaga is developing with great success an strategy based on facilitating ecosystems arising making use of balanced centricity strategy. Originality/value – The present paper re-defines the conceptualization of balanced centricity, considering it as an strategy to be developed at every level of the service ecosystem. Previous papers have never put together these concepts that build on the ecosystem theory to better understand and make easier the ecosystem management in both directions: for ecosystems fostering and to facilitate new ecosystems arising.
Keywords: Marketing; Service Dominant Logic; Balanced Centricity; Service ecosystem; Marketing de servicios